Las buenas acciones de Clifford - Bridwell, Norman (New York : Scholastic Book Services, 1980)
Clifford, un perro muy grande que siempre hace las buenas accionas mas bien de lo necesario, encuentra algo de su propio temano. (Clifford, a very big dog who always overdoes his good deeds, finds something to do that is his size.)
Translation of Clifford's good deeds.
Accelerated Reader
Keywords: Dogs -- Juvenile fiction; Perros -- Novela juvenil